Comparison of monounsaturated and polyunsaturated oils in continuous frying - T. P. Pantzaris (Grasas y Aceites)
Some work carried out by the Turbitak Marmara Research Centre and the Yildiz Technical University in Istanbul, in collaboration with the Palm Oil Research Institute of Malaysia, involved large scale laboratory frying trials of two monounsaturated oils (olive oil and palm olein) and two polyunsaturated oils (sunflower and soyabean) on potato chips (French fries). The oils were tested in parallel in separate 6-litre fryers on five consecutive days of eight hours and 14 batches of 150g potatoes each. At the end of each day the fryers were cleared of any sediment and topped up with fresh oil (about 250g). The performance of the oils was assessed by 11 physical and chemical tests viz. colour, smoke-point, foam height, free fatty acid content, fatty acid composition, iodine value, peroxide value, anisidine value, totox, polymer content and polar compounds. The monounsaturated oils scored higher in most tests and were clearly superior but in some tests such as colour and FFA the polyunsaturated oils scored higher. Single, simple tests as practised in many commercial establishments can be misleading and multiple tests need careful interpretation. The shelf-life of the chips was not assessed as this food is normally eaten within a short time of preparation. But the tests indicate that fried products intended for longer storage and wide distribution, will have a better shelf-life if fried in monounsaturated oils.